Influences of pH and Temperature on the Anaerobic Fermentation of Groundnut Shell and Cow Dung for Biogas Production - Mamman, P.; Saidu, M.; Busari, A.; Sadiku, S. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2022)
The increasing demand, high cost and health implications of using energy derived from hydrocarbon compound have necessitated the continuous search for alternative sources of energy. Groundnut shell (GS) and Cow dung (CD) as renewable source of energy supply have been proven to be very efficient. This study investigated the influences of operating parameters in anaerobic fermentation of GS and CD in the laboratory scale using the simple locally fabricated digesters labeled A-E of 4,000cm3 working volume. The temperatures were recorded one time daily using a thermometer that was fitted to the digester. The digesters were fed on a batch basis with the slurry of different mix ratio and operated at ambient temperature (28-40°C) for 30days. Digester A being the control containing 100% of CD have pH of 7.00 and 7.20 before and after digestion respectively. This shows that the pH values of cow dung was neutral before digestion and slightly alkaline after digestion while digester E containing 100% of groundnut shell also a control have pH of 7.10 and 7.20 respectively before and after digestion. The temperatures in the five digesters fluctuated optimally between 28°C and 40°C which conforms to the mesophilic range. Most microorganisms grow best under neutral pH conditions, since other pH values may adversely affect metabolism by altering the chemical equilibrium of enzymatic reactions, or by actually destroying the enzymes.  Low pH can cause the chain of biological reactions in fermentation to cease.